Narrativas bíblicas como um caminho para um entendimento pós-metafísico de Deus à luz da hermenêutica de Paul Ricoeur - Saldanha, Matheus Bonifácio de Souza (2021)
This work aims to present, in the light of Paul Ricoeur's biblical and philosophical hermeneutics, how the biblical narration points us to a path towards a post-metaphysical understanding of God. Ricoeur understands that the Bible was not written in a speculative language, but in a literary language that speaks about God; the Bible does not talk about God abstractly, it narrates the deeds of God in human history. Ricoeur addresses biblical texts as a field of mediation and deciphering the action of a God who allows himself to be narrated in the Holy Scriptures. The biblical God is, therefore, a narrated God. Thus, it becomes relevant to think and, also, to elaborate an understanding of the manifestations of God narrated in the founding documents of the Christian faith that take into account space-time aspects, not in a purely conceptual way, but phenomenal, in the relevance of the very history that we experience. For this, we will make use primarily of the ideas of the French thinker, through works that explain his hermeneutic compression, which will have an important role in the understanding of what is, for Ricoeur, the main text of the Sacred Scriptures that reveals to us the God of Israel, that is, the theophany of Exodus 3. Together with other interpreters of Ricoeurian philosophy and authors, we will seek to fulfill our objective, which is characterized as the search for a thinking God that is based on the biblical narration about this God. However, even considering the dimension of this task, we believe that in the development of this work, it will be possible to perceive that the nature of biblical narratives offers intriguing epistemological and ontological perspectives for the interpretation of the reality of God, however, without the intention of reducing the dimension of the divine mystery